1997
DOI: 10.1111/j.1600-0447.1997.tb09656.x
|View full text |Cite
|
Sign up to set email alerts
|

Phototherapy is a useful adjunct in the treatment of depressed in‐patients

Abstract: Phototherapy is regularly used in the treatment of seasonal affective disorder. There is evidence that it is also useful in the treatment of non-seasonal depression, but relevant controlled experiments are difficult to design. In this study we randomly assigned depressed in-patients to high and low levels of artificial light, the high levels exceeding those most commonly used in earlier reported trials. Both unipolar and bipolar depressions responded when phototherapy was used as an adjunct to pharmacotherapy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 8 publications
1
18
0
2
Order By: Relevance
“…32,58 Further, the combination of light regimens with antidepressant compounds such as imipramine, sertraline, and citalopram has been shown to significantly improve mood, with faster response rates than an antidepressant-only control group. [59][60][61][62][63] In addition, melatonin levels have also been found to show significant differences in patients with nonseasonal major depression when compared with healthy individuals. 64 Due to the very nature of nonseasonal depression and its multifactorial causes and symptoms, a purely chronobiological light-driven treatment regime would be difficult to apply.…”
Section: Nonseasonal Depressionmentioning
confidence: 99%
“…32,58 Further, the combination of light regimens with antidepressant compounds such as imipramine, sertraline, and citalopram has been shown to significantly improve mood, with faster response rates than an antidepressant-only control group. [59][60][61][62][63] In addition, melatonin levels have also been found to show significant differences in patients with nonseasonal major depression when compared with healthy individuals. 64 Due to the very nature of nonseasonal depression and its multifactorial causes and symptoms, a purely chronobiological light-driven treatment regime would be difficult to apply.…”
Section: Nonseasonal Depressionmentioning
confidence: 99%
“…Studies in the 1990s became the basis of a widely cited benchmark for BLT with light intensities of up to 10,000 lux and duration of 30 min/day. 22 Evidence 23 suggests that the melatonergic (MT [1] and MT [2]) and the 5-Hydroxytryptamine (5HT2C) serotonergic receptor subtypes are important modulators of circadian rhythmicity. Melanopsin, a short-wavelength, light-sensitive G-proteincoupled receptor located in human retinal ganglion cells, is known to transduce short-wavelength light signals into neural signals.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, the effect of BLT in non-seasonal depression has been controversial. While some controlled studies reported significant improvements, 2 others failed to do so. 3 Even if the improvement may be less than those seen in SAD, it can be assumed that at least some patients with non-seasonal depression respond to BLT.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike SAD, non-seasonal patients are more likely to have heterogeneous chronobiological patterns and could have either sleep phase advance or phase delay [28]. Of the 24 studies reviewed, one study demonstrated effective sleep phase delay by morning light timing and improved sleep length by aligning the timing of melatonin secretion [24] as well as enhancing mood [11], [24]. Given the scarce literature on light timing and mood, it is too soon to rule out the timing of light exposure (AM or PM) as insignificant in light treatment.…”
Section: Light Characteristicsmentioning
confidence: 99%
“…The photoperiod can be increased by five to six hours to reverse the seasonal changes using bright (2500 lux), full-spectrum light in the hours of morning, evening and at night [19]. Patients with Nonseasonal Affective disorder (NSAD) or MDD can also benefit from light treatments [20][21][22][23][24]. In fact bright-light therapy for MDD patients was 12-35% more beneficial than dim-light placebos or anti-depressants [25].…”
Section: Introductionmentioning
confidence: 99%